PENGARUH PERSEPSI EFIKASI DIRI SERTA MOTIVASI PEMBELAJARAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA DAN HASIL BELAJAR - Dwipani, Amelia; Asriati, Nuraini; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze : (1) the effects of self-efficacy on student learning outcomes of craft and entrepreneurship subject in X grade of IPA state Senior High School (SMAN) 3. (2) the effects og motivation on student learning outcomes of craft and entrepreneurship subject in X grade of IPA State Senior High School (SMAN) 3. (3) the effects of self-efficacy and learning motivation on student learning outcomes of craft and entrepreneurship subject in X grade of IPA State Senior High School (SMAN) 3. The research method used is the survey method. This study is quantitative research. The research samples were 70 student. The technique of measuring data used was a Likert scale, the data collectin tool used was a questionnaire. The data analysis technique used was multiple linear regression. The results of this study show that (1) there is an effect of self-efficacy on student learning outcomes in craft and entrepreneurship lesson in X grade of IPA at SMAN 3 Pontianak by 48,6%. (2) there is an effect of learning mitivation on student learning outcomes in craft and entrepreneurship lessons in X grade of IPA at SMAN 3 Pontianak by 64,9%. (3) there is an effect of self-efficacy and learning motivation on student learning outcomes in craft and entrepreneurship lessons in X grade of IPA at SMAN 3 Pontianak by 69,9%.Keyword : Self-Efficacy, Learning Motivation, Learning Outcomes